A RESPONSE OF AIDS FROM DE COMMUNITARY PROGRAMS OF SOCIAL SERVICES - Garcés, Jorge; Durá, Estrella (Anales de Psicología / Annals of Psychology)
In this paper we try to outline communitary programs to cope with A.I.D.S. We describe experiences and resources existing in the Comunidad Valenciana and U.S.A. for Information, Living together with others and Cooperation/ Participation Programs; we interpolate heuristics propositions for the coordination between Social Services and Health Services.